2013
DOI: 10.1007/s00068-013-0309-z
|View full text |Cite
|
Sign up to set email alerts
|

Computerized dynamic posturography analysis of balance in individuals with a shoulder stabilization sling

Abstract: Wearing a sling causes balance decompensation in almost one-third of healthy volunteers, and this is greater when worn in the non dominant hand, with double the number of falls. This has significant implications for patients having prolonged use of a sling. Consideration should be given to operative procedures or conservative management of shoulder pathology where sling use is required and promotion of the early discontinuation of sling use can be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The role of the upper limb in human postural control has previously been reported indirectly. It has been shown, for example, that axillary nerve blockage with anesthetics produces a 30% increase in body sway (Kjaergård et al, 1984 ), while immobilization of the upper limb with a sling reduce the performance in dynamic balance tests and increase the number of falls (Lui et al, 2013 ). The present study provides evidence that postural control and balance in adult subjects is impaired by upper limb dysfunction associated with the brachial plexus lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the upper limb in human postural control has previously been reported indirectly. It has been shown, for example, that axillary nerve blockage with anesthetics produces a 30% increase in body sway (Kjaergård et al, 1984 ), while immobilization of the upper limb with a sling reduce the performance in dynamic balance tests and increase the number of falls (Lui et al, 2013 ). The present study provides evidence that postural control and balance in adult subjects is impaired by upper limb dysfunction associated with the brachial plexus lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown the contribution of the upper limb to human postural control. Studies employing axillary nerve blockage with anesthetics (Kjaergård et al, 1984 ), upper limb immobilization (Coleman and Clifft, 2010 ; Lui et al, 2013 ) or fatiguing arm exercises (Douris et al, 2011 ) have shown that decreases in upper limb function negatively affect postural control and balance, as observed by increases in body sway or reduced performance in dynamic balance tests. Altered postural control and body alignment were also found in individuals who have undergone radical mastectomy, which usually results in lymphatic edemas, restriction of movement and strength loss in the arms (Rostkowska et al, 2006 ; Ciesla and Polom, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Posturography is typically used to evaluate the health status of patients suffering from musculoskeletal and neurological disorders, e.g. victims of accidents [11], [12], hemiparetic patients [13], people with cerebellar diseases [14], [15], Parkinson's disease [16]- [18] or disorders within the vestibular system [19]- [21]. The authors of this article, however, concentrate on its uses in the context of postural symmetry assessment of patients undergoing rehabilitation after total hip arthroplasty.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In a similar way the scaled covariance coefficient for the sagittal signal components was defined [6]: (12) where:…”
Section: B Postural Symmetry Assessment Using Covariance Coefficientmentioning
confidence: 99%
“…This combination of factors may lead to progressive failure at the bone implant interface, implant migration and fracture displacement. [1][2][3][4] Indications for surgery vary a great deal from study to study, and are often ill defined. Identification of risk factors for poor outcomes is important, including the identification of poor bone mineral density and the possibility of developing avascular necrosis.…”
Section: Introductionmentioning
confidence: 99%